Recombinant HMG1 Protein Produced in Pichia pastoris: A Nonviral Gene Delivery Agent. (April 1997) - Mistry, A.R.; Falciola, L.; Monaco, L.; Tagliabue, R.; Acerbis, G.; Knight, A.; Harbottle, R.P.; Soria, M.; Bianchi, M.E.; Coutelle, C.; Hart, S.L.
This paper describes the production of a recombinant protein from the expression system based on the methylotrophic yeast Pichia pastoris . Efficient production of rat high-mobility-group 1 (HMG1) protein was obtained using the system. Two forms of HMG1 were secreted into the culture medium: a 24.5-kDa species corresponding to the native HMG1 and a 32-kDa glycosylated derivative. Non-glycosylated recombinant HMG1 was purified easily and shown to possess the same DNA-binding properties as HMG1 purified from calf thymus. Plasmid DNA complexed to the recombinant HMG1 is taken up by a variety of mammalian cells in culture. Transient expression of a luciferase reporter gene was observed. Under selective conditions, stable expression of a neomycin gene was established as a result of integration into the genome. HMG1-mediated gene delivery was as efficient as calcium phosphate-mediated transfection but without associated cell damage. In addition, stable transfectants obtained after selection for G418 resistance usually integrated only one copy of the transfected DNA in contrast to the high unpredictable number obtained by the calcium phosphate method. HMG1 transfection complexes were not toxic to cultured cells, even at high concentrations.